(untitled) (Global Journal of Human-Social Science, 2025)
Philosopher c est apprendre mourir Socrates 1 Montaigne 1533-1595 Was a man full of paradox a most mod ern thinker under the garb of one of the greatest 16th century philosophers See also Masud Khan 1975 Reading his essays I was impressed like others by his psychological mindedness and also that some 320 years before Freud he intuitively discovered many of the findings of psychoanalysis and the activity of the unconscious This paper aims at acquainting an analytically minded audience with the scope of Montaigne s discoveries as there are very few papers written about the essays by mental health professionals I discovered that there are over 300 references to his work in the Pep-web either in papers written which mention him in passing him or in articles quoting from his writings Yet there are only a handful of analytic papers devoted to his work mostly in the French analytic journals and only two articles in the English psychoanalytic literature Canestri 2009 and Wolf and Gedo 1975 though there are of course many books written about him in the classical literature section One of the most famous is Montaigne en Mouvement by Jean Starobinski 1982 which has been translated into English